Diagnostic approach for patients with unidentified fever according to the classical criteria of fever of unknown origin in the field of autoimmune disorders. Issue 4 (2nd October 2019) - Watanabe, Rina; Sakuraba, Hirotake; Hiraga, Hiroto; Kishida, Dai; Ota, Shinji; Hasui, Keisuke; Kikuchi, Hidezumi; Akemoto, Yui; Tanaka, Nahoko; Maeda, Takato; Murai, Yasuhisa; Yoshida, Shukuko; et al.
Abstract: Fever of unknown origin (FUO) is caused by various diseases, making differential diagnosis difficult. This study aimed to determine the clinical features of patients with FUO for use in daily medical practice. Medical records of patients who first visited our department for FUO between January 2008 and December 2017 were reviewed. We classified the diagnostic categories as infection, non-infectious inflammation, neoplasm, others, and unidentified through definitive diagnosis and compared the clinical characteristics of patients who fulfilled the criteria of classical FUO and those who did not. The most prevalent diseases in patients who fulfilled the criteria were adult-onset Still's disease, Behçet's disease (BD), and polymyalgia rheumatica, which do not have any specific image inspection or specific serological markers. BD and familial Mediterranean fever were most prevalent in patients who did not fulfill the criteria. All neoplasms fulfilled the criteria of classical FUO. The most useful diagnostic procedure was determined according to the criteria of each disease. The key factor that did not fulfill the criteria was periodic fever continuing for less than 3 weeks. When examining patients with FUO, we should strictly diagnose in accordance with the criteria of each disease and consider diseases that cause periodic fever.